Religious diversity in late antiquity - Gwynn, David M. (David Morton), 1975-; Bangert, Susanne; Lavan, Luke. (Leiden ; Boston : Brill, 2010)
Contributors are David M. Gwynn, Susanne Bangert, Jodi Magness, Zeev Weiss, Shimon Dar, Michel-Yves Perrin, Bryan Ward-Perkins, Lukas Amadeus Schachner, Arja Karivieri, Carla Sfameni, Claude Lepelley, Mark Humphries, Elizabeth Jeffreys, and Isabella Sandwell. --Book Jacket.
Religious diversity in late antiquity : an introduction / David M. Gwynn and Susanne Bangert -- Religious diversity in late antiquity : a bibliographic essay / David M. Gwynn -- Jews and Samaritans -- Third century Jews and Judaism at Beth Shearim and Dura Europus / Jodi Magness -- Artistic trends and contact between Jews and 'others' in late antique Sepphoris : recent research / Zeev Weiss -- Archaeological aspects of Samaritan research in Israel / Shimon Dar -- Orthodoxy and heresy -- The limits of the heresiological ethos in late antiquity / Michel-Yves Perrin -- Archaeology and the 'Arian controversy' in the fourth century / David M. Gwynn -- Where is the archaeology and iconography of Germanic Arianism? / Bryan Ward-Perkins -- Popular piety -- The archaeology of pilgrimage : Abu Mina and beyond / Susanne Bangert -- The archaeology of the stylite / Lukas Amadeus Schachner -- Magic and religion -- Magic and syncretic religious culture in the East / Arja Karivieri -- Magic in late antiquity : the evidence of magical gems / Carla Sfameni -- Sacred and secular -- The use of secularised Latin pagan culture by Christians / Claude Lepelley -- The sacred and the secular : the presence or absence of Christian religious thought in secular writing in the late antique West / Mark Humphries with David M. Gwynn -- Literary genre or religious apathy? : the presence or absence of theology and religious thought in secular writing in the late antique East / Elizabeth Jeffreys -- John Chrysostom's audiences and his accusations of religious laxity / Isabella Sandwell.
English text; abstracts in French.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Religion -- History; Religions -- History; Civilization, Ancient; RELIGION -- History; Civilization, Ancient; Religion; Religions; Electronic books; History